Assessment of heart rate variability and reaction time in traffic policemen - Saranya Kuppusamy; Dhanapal Niraimathi; Nitin Ashok John (International Journal of Medical Research and Review, 2016)
Introduction: Air Pollution can have a deleterious effect on cardiovascular function and cognition. Heart rate variability (HRV), which is a non-invasive and objective measure of cardiac autonomic function, is a cardiovascular risk predictor. Reaction time is a simple method of assessing the perceptual-cognitive processing capability of the central nervous system. Hence, the aim of the study was to assess the heart rate variability and reaction time in traffic police officers of Puducherry.Methods: Fifty-five age and BMI matched traffic police and healthy controls were recruited. Basal cardiovascular parameters; basal heart rate, systolic and diastolic blood pressure (BHR, SBP, DBP) were assessed. Short term HRV analysis was done. Time and frequency domain indices were computed. Simple and Choice Auditory and Visual reaction time (SART, CART, SVRT, CVRT) were measured.Results: BHR and DBP were significantly increased in traffic police. Time domain indices (Mean RR, SDNN, RMSSD, pNN50) were significantly reduced in traffic police. In frequency domain, Total Power was significantly reduced. LF-HF ratio was increased, though not significant. SVRT was significantly delayed in traffic police. CVRT, SART and CART were delayed in traffic police though not significant.Conclusion: Traffic police have decreased HRV with increased sympathetic and decreased vagal tone, and delayed reaction time.